Return to Sport After Arthroscopic Superior Labral Anterior-Posterior Repair: A Systematic Review. (November 2019) - Thayaparan, Aarabi; Yu, James; Horner, Nolan S.; Leroux, Timothy; Alolabi, Bashar; Khan, Moin
Context: Superior labral anterior-posterior (SLAP) lesions often result in significant sporting limitations for athletes. Return to sport is a significant outcome that often needs to be considered by athletes undergoing the procedure. Objective: To evaluate return to sport among individuals undergoing arthroscopic SLAP repair. Data Sources: Four databases (MEDLINE, EMBASE, PubMed, and Cochrane) were searched from database inception through January 29, 2018. Study Selection: English-language articles reporting on return-to-activity rates after arthroscopic SLAP repairs were included. Study Design: Systematic review. Level of Evidence: Level 4. Data Extraction: Data including patient demographics, surgical procedure, and return to activity were extracted. The methodological quality of included studies was evaluated using the Methodological Index for Non-Randomized Studies (MINORS) tool. Results: Of 1938 screened abstracts, 22 articles involving a total of 944 patients undergoing arthroscopic SLAP repair met inclusion criteria. Of the total included patients, 270 were identified as overhead athletes, with 146 pitchers. Across all patients, 69.6% (657/944 patients) of individuals undergoing arthroscopic SLAP repair returned to sport. There was a 69.0% (562/815 patients) return to previous level of play, with a mean time to return to sport of 8.9 ± 2.4 months (range, 6.0-11.7 months). The return-to-sport rate for pitchers compared with the return-to-activity rate for nonpitchers, encompassing return to work and return to sport, was 57.5% (84/146 patients) and 87.1% (572/657 patients), respectively, after arthroscopic SLAP repair. Conclusion: Arthroscopic SLAP repair is associated with a fair return to sport, with 69.6% of individuals undergoing arthroscopic SLAP repair returning to sport. SLAP repair in pitchers has significantly decreased return to sport in comparison with nonpitching athletes. Athletes on average return to sport within 9 months postoperatively.